RESPONSE OF GROWTH AND YIELD CHARACTERS OF TOMATO (Solanum lycopersicum L.) VARIETIES TO SEASONS IN GREENHOUSE CONDITION IN LAM DONG PROVINCE - Hai Chau, Mai; Xuan Chinh, Ngo (Journal of Forestry Science and Technology, 2021)
Field experiments were conducted at Lien Nghia Town, Duc Trong district, Lam Dong province to investigate the performance of tomato (Solanum lycopersicum L.) varieties during rainy and dry seasons in greenhouse condition. The experiment was set up as one - way factorial design (Randomized Complete Block Design), including 4 different varieties (Lahay 344, Labell, Clay and Anna) with 3 replications spreading over two seasons: rainy season from March to October 2018 and dry season from October 2018 to April 2019. The results showed that the variety and season signifcantly (P<0.01) eﬀects on yield characteristics (individual fruit yield, fruit yield and marketable fruit yield) during the year of the experiments. Two varieties of Lahay 344 and Labell gave the highest quality and productivity in all varieties participating experiments, accounting for 205.51 tons per ha and 222.33 tons per ha, respectively. The Anna variety produced lowest yield in both seasons. However, the Lahay 344 gave the best choice for tomato’s production in greenhouse condition based on their properties such as large fruit weight and stable quality during the crop, hard peduncle, less disease, flattened fruit shape, nice color and adapting to climate and cultivated conditions in Duc Trong district, Lam Dong province.